Sompa dalam Perkawinan Orang Bugis Bone di Desa Marga Jaya Kecamatan Rarowatu Utara Kabupaten Bombana - Wahyu Indah Permatasari; Hasniah Hasniah; Hartini Hartini (JURNAL KABANTI: Kerabat Antropologi, 2022)
This study aims to determine and determine and describe the determination of giving sompa and the meaning of sompa in Bugis marrianges in marga Jaya villace, North Rarowatu District, Bombana Regency, ethnographic method. The result showed trat the tradition of determining ompa in the marriage of the Bugis Bone in Marga Jaya Village still sees the equality of social status for the bride to be. In addition, this tradition must be carried out by the Bugis Bone as a sign that there are conditions that must be carried out before marriage. Thus, the high demand for sompa and panai money is in accordance with the request from the woman’s family through a spokesperson who was sent to participate in the application or asaessment program. The simbols in the sompa mean that in the future their domestic life will remain safe, harmonious and full of love.